LMD-03. Single cell analysis reveals how therapy remodels the tumor microenvironment in melanoma CNS metastases and uncovers a novel predictor of improved survival. (9th August 2021) - Smalley, Inna; Chen, Zhihua; Phadke, Manali; Li, Jiannong; Yu, Xiaoqing; Wyatt, Clayton; Evernden, Brittany; Messina, Jane; Sarnaik, Amod; Sondak, Vernon; Zhang, Chaomei; Law, Vincent; et al.
Abstract: We interrogated the microenvironment of 43 clinical samples from melanoma skin, brain (MBM) and leptomeningeal metastases (LMM) using single-cell RNA-seq analysis to determine how therapeutic intervention shaped the immune environment and affected patient survival. LMM is a poorly-characterized, devastating complication of late-stage disease, typically refractory to treatment and associated with dismal survival time. Analysis of serial specimens over the course of therapy demonstrated reductions in melanoma cells and macrophages, coupled with increased levels of T cells and dendritic cells in the CSF of a rare extraordinary responder, whereas typical poor survivors showed no improvement in T cell responses. In MBM patients, both targeted therapy and immunotherapy was associated with increased immune infiltrate. Treatment with targeted therapy was associated with an enrichment of CD8 T cells, while immunotherapy was associated with a more diverse lymphocyte landscape and higher numbers of antibody-producing cells. These findings were confirmed by multiplex-IF staining of patient specimens and using an immune-competent mouse model of MBM. Interestingly, a history of prior radiation therapy was associated with a diminished myeloid compartment. Although immune infiltrate was significantly lower in the brain compared to skin tumors, the phenotypic make-up of the lymphocyte compartment was quite similar, suggesting that the immune cells may have trafficked from the periphery to the brain post-therapy. Correlation analysis across the entire immune landscape identified the presence of a rare, novel population of dendritic cells (DC3s) to be correlated with increased overall survival, regardless of disease site/treatment. The presence of DC3s positively regulated the immune environment of both patient samples and preclinical melanoma models through modulation of activated T cells and MHC expression in the tumor. Overall, we present the first ever comprehensive single-cell atlas of the tumor microenvironment in melanoma CNS metastases in response to therapy.